Cybersecurity of long-range wide-area network - Chia, Faith Su Chi (2018)
The increasing popularity of Internet of Things (IoT) devices has led to increased interest in Low Power Wide Area Networks (LPWANs), which allow IoT devices to communicate over long ranges using little power. One popular LPWAN technology is LoRa (short for Long Range). While useful, LPWAN technology poses a security risk due to the broadcast nature of wireless communications. Transmissions can be received by users other than the intended recipient. In particular, a delay attack can be implemented on unsuspecting end nodes. Implementation of a delay attack is especially trivial as packet decryption is not required, and the tools required are not specialized equipment and can be easily purchased. Previous research has shown the feasibility of implementing a delay attack on LoRa nodes. This project establishes that the signal detection component of the delay attack can be done fast enough to implement a delay attack.